Teaching the Four Language Skills in Primary EFL Classroom: Some Considerations - Kurniasih, Eka (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2011)
English teachers in Indonesian primary schools are often in doubt about the 'what' and the 'how' to teach because most English teachers training colleges do not provide them with specialized training in how to meet the needs of primary school students; TEYL is a new and highly dynamic field; in the curriculum of primary schools in Indonesia English is a local content, and thus the National Education Ministry does not provide English syllabus for primary school. Since the objective of teaching English in primary school is to provide a good basis for communicative competence as a foundation to study it in a secondary school; the development of the four language skills should be made the focus of all learning activities. This paper provides some guidelines, which are adapted from some publications and discussions concerning TEYL for teaching the four language skills in primary schools.